A series of new manganese thioarsenates(v) based on different unsaturated [Mn(amine)x]2+ complexes1. Issue 37 (7th October 2015) - Zhou, Jian; Tan, Xiao-Feng; Liu, Xing; Qing, Miao; Zhao, Rong-Qing; Tang, Qiuling
<x xml:space="preserve">Abstract</x> Different unsaturated [Mn(amine)x]2+ complexes have a significant structure directing effect on the structures of manganese thioarsenates(v) under similar solvothermal conditions.